Physics beyond the standard model - Rosenfeld, R. [UNESP] (My University, 2016)
In these three lectures I review the need to go beyond the Standard Glashow-Weinberg-Salam Model and discuss some of the approaches that are explored in this direction.
Keywords: Beyond the standard model; Effective lagrangian; Hidden sector; Lectures; Particle physics; Supersymmetry